Sorption of Pyrene by Clay Minerals Coated with Dissolved Organic Matter (DOM) from Landfill Leachate - Pingxiao Wu; Yong Wen; Yun Xiang; Jianbing Zhou; Jianwei Du; Nengwu Zhu; Ping Li (Journal of Chemistry)
Interactions of dissolved organic matter (DOM) from landfill leachate with clays could affect significantly the fate of hydrophobic organic compounds (HOCs) in soils. The complexes of montmorillonite (MT) and kaolinite (KL) with DOM extracted from landfill leachate were prepared under controlled conditions, termed CMT and CKL, respectively. The bare clays and their complexes were characterized by powder X-ray diffraction (XRD), Fourier transform infrared (FTIR), thermogravimetry (TG), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). Batch experiments were designed to investigate the sorption behavior of pyrene onto the clays in the presence of DOM. The maximum sorption capacities of pyrene on MT, CMT, KL, and CKL were 22.18, 38.96, 42.00, and 44.99 μg·g−1, respectively, at the initial concentration of 1000 ± 150 μg·L−1. The sorption isotherms of pyrene by the bare clays followed the Henry model well, whereas the Freundlich sorption isotherm provided a better fit to the equilibrium data of the sorption by the complexes. The role of montmorillonite and kaolinite complexes with DOM in the retention of pyrene in soils was different. This may be due to the different crystal structures between montmorillonite and kaolinite.